Iraq public exposuring to foreign satellites and its effect on the cultural identity - محمد حسين علوان (College of Education for Women, 2019)
The summary of this study is to identify the relation ship between exposuing of the public to foreign satellites and the degree of cultural of Iraqi public . the danger Iraqi public exposure to foreign satellite specially some groups of the public are still own limited culture and ideology without enough conscious to attitude of society . such people cun easily be controlled by satellites , because these satellites may be the only cultural source for them which may badly affect their behaviour . This study also aims to identify the level of Iraqi people exposure to foreign satellites and the types and motivations of that exposure , then to realize the relationship between exposing to foreign satellites and the cultural level of the Iraqi public . This study is descriptive that aims to analyze a definite study which is studying available facts or attitudes in addition of describing negate relationship to discover the facts related and generalize them .